2014
DOI: 10.1080/09537287.2014.927931
|View full text |Cite
|
Sign up to set email alerts
|

A study of the use of business improvement initiatives: the association with company size and level of national development

Abstract: This paper investigates the awareness, use and effectiveness of improvement initiatives in organisations of different sizes and in different countries. In particular, comparisons are made between large firms and SMEs, between organisations in the developing and developed worlds and between organisations in China and India and the rest of the developed world. A questionnaire survey of 453 organisations across 44 countries was conducted with the findings indicating that there are significant differences in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This is evidenced by the effectiveness of other systematic approaches to problem solving and improvement such as PDCA (Adebanjo et al, 2015;Deming, 1993) and DMAIC (Ghosh and Maiti, 2014;Garza-Reyes et al, 2014). The importance of following a structured and integrated approach to operations improvement has been widely discussed in the academic literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the effectiveness of other systematic approaches to problem solving and improvement such as PDCA (Adebanjo et al, 2015;Deming, 1993) and DMAIC (Ghosh and Maiti, 2014;Garza-Reyes et al, 2014). The importance of following a structured and integrated approach to operations improvement has been widely discussed in the academic literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are they three of the four countries In the BRIC nations (Russia being the fourth) recognised as fast growing economies, there is already evidence that organisations in these countries have differentiated themselves from those in other developing countries. A study by Adebanjo et al (2015) found that organisations in China and India were more likely to adopt a range of business improvement tools and techniques compared to organisations in other developing countries. The findings from this study provide a collective view of whether manufacturers in these three countries are acquiring and exploiting innovative capabilities, irrespective of differences in culture and other national characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Achanga et al (2006) and Shah and Ward (2003) report SMEs have a lower take-up rate of LPS practices than LEs. According to Adebanjo et al (2014), LEs are more likely to adopt improvement initiatives such as lean related initiatives when compared to SMEs. Bhamu and Sangwan (2014) stress that SMEs encounter difficulties in adopting LPS and have concerns over the cost of LPS implementation.…”
Section: Lean Production System (Lps)mentioning
confidence: 99%
“…Hence, teaching and educating SME managers and employees have been considered as the key tasks in the implementation of LPS (Gunasekaran andLyu 1997, Dombrowski et al 2010). Business assistance from external agencies is also required when implementing a new production system like LPS in SMEs (Adebanjo et al 2014, Panizzolo et al 2012). …”
Section: Lean Production System (Lps)mentioning
confidence: 99%